Hubungan Antara Dukungan Keluarga Inti DenganProkrastinasi Akademik Mahasiswa - ISMUNANDAR, Thaufik Radhityawan (2016)
Many university students complaining on not being able to manage their time well, when to begin and to do something, so, time which should be useful is wasted useless. Procrastination in beginning or finishing tasks faced, lateness in doing the tasks, time gap between plans and actual performance, doing other more pleasant activities than doing the tasks that must be done are aspects of academic procrastination. One of external factors influencing the university students in doing the academic procrastination is the nuclear family's support. Every kind of family's support has aspects such as being informative, emotional care, instrumental help and assessment help. The objective of this research was to know the correlation between the nuclear family's support and the academic procrastination in the university students. This research was conducted at psychology faculty of Muhammadiyah University of Surakarta with subjects were the students as many as 231 people determined by using the technique of non-probability purposive sampling. The measurement instruments used were the scale of the nuclear family's support and the scale of the academic procrastination. From the results of the product moment correlation analysis, it was obtained the result of the coefficient of correlation as much as -0.442 with p<0.01 that showed that there was a negatively significant correlation between the nuclear family's support and the academic procrastination, therefore, the hypothesis was accepted. It meant that the higher the nuclear family's support, the lower the academic procrastination would be, in contrary, the lower the nuclear family's support, the higher the academic procrastination would be. The effective contribution of the variable of nuclear family's support on the variable of academic procrastination was as much as 19.5%.